Manganese(III)-Based Oxidative Cyclization of N-Aryl-2-oxocycloalkane-1-carboxamides: Synthesis of Spiroindolinones - Katayama, Shintaro; Nishino, Hiroshi (Synthesis, 2019)
The Mn(III)-based oxidative cyclization of twenty-five N-aryl-2-oxocycloalkane-1-carboxamides is investigated. The reactions progress efficiently to give the desired spiro[cycloalkane-1,3′-indoline]-2,2′-diones in high to quantitative yields. The easy conversion of the carbonyl functional group of one of the indoline products, 1′-methylspiro[cyclohexane-1,3′-indoline]-2,2′-dione, is also demonstrated.
Keywords: spiro[cycloalkane-1,3′-indoline]-2,2′-diones; oxidative cyclization; 5-exo cyclization; radicals; heterocycles; spiro compounds; indolinones